Physician Multi-Site Practice in China: Doctor practices, public views and legitimacy based on a controversial case - Wayne Tsien; Jing-Bao Nie; Robin Gauld (ACHSM, 2023)
Aim: Physician multi-site practice (PMP), or dual practice, is commonplace worldwide. Since the mid-2000s, the Chinese government has issued a series of laws and regulations to promote PMP with a goal of improving access to high-quality medical services. However, PMP is widely conducted illegally in China, i.e., without official registration of practicing doctors. This article provides a more nuanced understanding of PMP in China. Approach: This article takes a case study approach. It presents a high-profile case exposed through Chinese social media as well as public perceptions through the lens of online comments given by over thirty thousand netizens on a nationally controversial case. Findings: Netizens saw benefits to PMP despite being illegal. A culturally-rooted Chinese construction of the triple concepts of 'Qing' (sensibility, feeling or sentiment), 'Li' (propriety, norm or reason) and 'Fa' (rule, regulation or law) is employed to explore the issue of legitimacy of PMP in the Chinese context and explain why PMP has not yet been implemented effectively, and why members of the general public strongly support illegal PMP. Conclusion: While doctors and the public support illegal PMP, it will be challenging for the Chinese government to gain traction with official PMP policy.